Global food systems: Can foresight learn from hindsight? - Brooks, Karen; Place, Frank (Elsevier, 2019)
Construction of plausible scenarios for alternative futures of global food systems requires an understanding of how the past led to the present, and the past's likely relevance to the future. Policy actions affected the past, but are very difficult to foresee. Among those that most shaped global food systems in the last half century are measures that fostered productivity growth, expansion of trade, and the interlinkage of agricultural and environmental policies. Scenarios for global food systems, including those using the quantitative tools of the CGIAR's Global Futures and Strategic Foresight modeling approach, explore alternative assumptions in these three areas, among others. Hindsight can inform foresight by highlighting key elements of the past and forcing transparent examination of whether and how these elements will shape the future.